Nursing Assistant Students’ Digital Cultural Intelligence and Clinical Adaptability in a North African Health College: A Cross-Sectional Study - Oulhiq, Ridouane; W, Shi ching; Ratt, Pichayapor; Brain, Maurizio Martin Cavani (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study examined the predictive relationship between digital cultural intelligence and clinical adaptability among nursing assistant students at a health sciences college in Morocco. Methodology: A cross-sectional design was employed with 287 students who had completed at least one clinical placement. Data were analysed using partial leas squares structural equation modellingi (PLS-SEM) to test a theory-driven conceptual framework. Measurement model evaluation confirmed satisfactory reliability and validity (CR > 0.90; AVE > 0.50; HTMT < 0.85). Structural analysis revealed that digital cultural intelligence significantly predicted clinical adaptability (β = 0.64, p < 0.001), explaining 41% of the variance (R² = 0.41). Predictive relevance was supported (Q² = 0.29), and robustness checks using covariance-based SEM confirmed acceptable model fit indices. Main Findings: The findings indicate that the capacity to navigate culturally diverse interactions within digitally mediated healthcare environments is a substantial determinant of adaptive clinical reasoning, flexible communication, and ethical responsiveness. By empirically validating digital cultural intelligence as a multidimensional construct in vocational nursing education, this study advances theoretical integration between intercultural competence and adaptive expertise frameworks. Novelty/Originality of this study: This study contributes Global South evidence to international nursing education research and provides a predictive model for curriculum innovation in digitally transitioning healthcare contexts.